Optimizing Finishing Pig Performance and Sustainability: The Role of Protein Levels and Eco-Friendly Additive - Weihan Zhao; Kyejin Lee; Inho Kim (Animals)
This study contributes to promoting green farming and achieving sustainable pork production. Especially under the conditions of resource scarcity and rising environmental demands, efficient and eco-friendly feeding strategies have become key to industry development. We evaluated the effects of supplementing an eco-friendly additive (EFA) in diets with normal and low protein (−2% CP) levels on growth performance, nutrient digestibility, gas emission, fecal score, meat quality, and blood profile in finishing pigs. In this 10-week (70-day and 7-day adaptation period) feeding experiment, 200 crossbred pigs [Duroc × (Landrace × Yorkshire)] with an initial average body weight (BW) of 55.05 ± 3.35 kg were used. The pigs were randomly assigned to four treatment groups in a 2 × 2 factorial arrangement, with five pigs per replicate group, including two gilts and three barrows per pen, and each treatment group was repeated 10 times. The experimental treatments included the following: two protein levels (normal CP and −2% CP) and two EFA levels (0% and 0.5% EFA). The results showed that pigs fed high-protein + EFA diets had a significantly higher ADG from weeks 0–5 compared to the high-protein control group (p < 0.05). From weeks 5–10 and overall, both high-protein + EFA and low-protein + EFA groups had a higher ADG than the low-protein − EFA group (p < 0.05). At week 10, the low-protein + EFA group showed significantly higher nitrogen digestibility and significantly lower ammonia emissions compared to the high-protein − EFA group (p < 0.05). Both EFA supplementation and protein level had significant effects on ammonia emissions. The fecal score was not significantly affected (p > 0.05). In blood profiles, NPY was higher in the high-protein + EFA group than in the low-protein − EFA group (p < 0.05). In terms of meat quality, both EFA-supplemented groups had a higher WHC compared to the low-protein − EFA group, while the high-protein + EFA group had a greater LMA (p < 0.05) and lower drip loss on day 7 after slaughter (p < 0.05). In conclusion, supplementing low-protein diets with EFA can effectively enhance the growth performance of finishing pigs, mitigate environmental pollution, and offer feeding advantages while lowering feed costs.